El arte de imprimir los oficios tipográficos en la ciudad de San José, 1830-1960 - Samper K., Mario (2000)
The article explores the development of typographic labor in San Jose, Costa Rica, from the introduction and initial diffusion of printing in 1830, until 1960, when the technical and social organization of typographic work changed markedly